2014
DOI: 10.1007/s13300-014-0076-9
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Degludec Versus Insulin Glargine in Type 1 and Type 2 Diabetes Mellitus: A Meta-Analysis of Endpoints in Phase 3a Trials

Abstract: IntroductionInsulin degludec (degludec) is a basal insulin with an ultra-long, stable action profile and reduced pharmacodynamic variability. Seven phase 3a trials compared degludec with insulin glargine (glargine). Patient-level meta-analyses were performed to obtain a comprehensive overview of differences between the insulin preparations, possible because consistent outcome definitions were utilized.MethodsThree categories of trials were analyzed: basal–bolus-treated type 1 diabetes mellitus (T1DMB/B), insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
3
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(122 citation statements)
references
References 19 publications
7
105
3
7
Order By: Relevance
“…The superior HbA 1c reduction achieved with BIL is noteworthy, since noninferiority has usually been observed in basal insulin treat-to-target trials (16)(17)(18). The FSG levels in glargine-treated patients were well within ranges reported in many treat-to-target trials, whereas BILtreated patients had greater reduction in FSG compared with glargine (19)(20)(21).…”
Section: Discussionmentioning
confidence: 73%
“…The superior HbA 1c reduction achieved with BIL is noteworthy, since noninferiority has usually been observed in basal insulin treat-to-target trials (16)(17)(18). The FSG levels in glargine-treated patients were well within ranges reported in many treat-to-target trials, whereas BILtreated patients had greater reduction in FSG compared with glargine (19)(20)(21).…”
Section: Discussionmentioning
confidence: 73%
“…This was directly investigated in two studies showing no significant difference in the rate of diurnal confirmed hypoglycaemia in patients with T1D or T2D [14,16]. Further meta-analyses confirmed that the reduction in nocturnal confirmed hypoglycaemia was not accompanied by increased rates of daytime confirmed hypoglycaemia in pooled T1D, pooled T2D and pooled insulin-naïve T2D [23]. The trial protocol for insulin-experienced patients required that those who were switching from twice-daily to once-daily insulin dosing administer their total pretrial basal insulin dose in the IDeg arm, but reduce the dose by 20-30% in the IGlar arm (as per the prescribing information).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A meta-analysis of results from phase 3 trials suggests that the efficacy, in terms of lowering glycated hemoglobin (A1C), of IDeg and Gla-100 was similar in patients with T2DM [45]. Hypoglycemia event outcomes with IDeg compared with Gla-100 have been reported from the BEGIN series of phase 3 trials, in which confirmed hypoglycemia was defined as a composite of episodes with a recorded self-monitored blood glucose (SMBG) value of less than ~54 mg/dl (3.1 mmol/l) and severe episodes were defined as those requiring assistance.…”
Section: Hypoglycemia In T2dmmentioning
confidence: 99%
“…In their meta-analysis of phase 3 trials of IDeg versus Gla-100, Vora et al reported that the two agents had similar efficacy in terms of reduction of A1C in T1DM patients [45].…”
Section: Insulin Degludecmentioning
confidence: 99%